The Effectiveness of the Gobak Sodor Game-Based Unplugged Coding Model in Improving Computational Thinking Skills Among Fifth-Grade Students - Tegar Arif Saputra (Insights: Journal of Primary Education Research, 2025)
Computational thinking skills are an important competency for elementary school students, but their implementation still faces limitations in digital resources and the need for concrete and contextual learning models. This study aims to test the effectiveness of the unplugged coding model based on the traditional game Gobak Sodor in improving the computational thinking skills of fifth-grade students. This study used a quantitative approach with a quasi-experimental method through a nonequivalent pretest–posttest control group design. The study sample consisted of 56 students divided into experimental and control groups. Data were collected using a computational thinking ability essay test that included indicators of decomposition, pattern recognition, abstraction, algorithm design, and debugging. Data were analyzed using descriptive statistics and ANCOVA with pretest scores as covariates. The results showed that the experimental group achieved a higher increase in computational thinking skills than the control group. The ANCOVA results showed that the Gobak Sodor-based unplugged coding model had a significant effect on students' computational thinking skills (F = 49.834; p < 0.001), with a large effect size (partial eta squared = 0.485; Cohen's d = 1.12). Thus, the unplugged coding model based on the traditional game Gobak Sodor is effective in improving elementary school students' computational thinking skills compared to conventional learning.